2021
DOI: 10.3390/life11030194
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Internet Addiction among Hungarian High School Teachers

Abstract: The extensive availability of internet has led to the the recognition of problematic internet use (so called internet addiction, IA) mostly involving adolescents. There is limited data about the prevalence of IA in adults. Here we present a study focusing on the prevalence and risk factors of internet addiction among high school teachers. Overall 2500 paper-based questionnaires were successfully delivered and 1817 responses received (response rate of 72.7%). In our study 1194 females (65.7%) and 623 males (34.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 32 publications
(39 reference statements)
4
16
2
4
Order By: Relevance
“…Based on our results, about one fifth of our high school students suffered from internet addiction, which is significantly higher than the estimated overall pooled prevalence of 7% in the general population [ 31 ]. However, based on very recent data, IA prevalence can be much higher among adolescents, which is in line with our results [ 7 , 17 , 28 , 30 , 31 , 32 , 33 ]. A recent study showed a rate of 15.5% of problematic internet users in a representative sample of 16-year-old Hungarians, which is nearly comparable to our findings [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Based on our results, about one fifth of our high school students suffered from internet addiction, which is significantly higher than the estimated overall pooled prevalence of 7% in the general population [ 31 ]. However, based on very recent data, IA prevalence can be much higher among adolescents, which is in line with our results [ 7 , 17 , 28 , 30 , 31 , 32 , 33 ]. A recent study showed a rate of 15.5% of problematic internet users in a representative sample of 16-year-old Hungarians, which is nearly comparable to our findings [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…As there are no clear diagnostic criteria for internet addiction, it is highly recommended to measure excessive internet use with a continuous questionnaire [ 12 ]. We chose the Problematic Internet Use Questionnaire (PIUQ) because its structure tightly adheres to the proposed diagnostic criteria for internet addiction and was created based on the clinometric and psychometric analysis of Young’s internet addiction test, independently validated by several groups and used in our previous published work [ 7 , 28 , 29 , 30 ]. The questionnaire contains 18 items, each scored on a 5-point Likert-type scale ranging from 1 (never) to 5 (always).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that that excessive problematic Internet use behaviors should be considered as contributing risk factors in terms of teachers’ psychological distress, particularly in the online teaching context during COVID-19. In explaining the role of PIU among teacher populations, certain characteristics (i.e., excessive Internet use and workaholic tendencies) should be considered in the context of COVID-19 [ 70 , 71 , 72 , 73 , 74 ]. Specifically, teachers using the Internet for 5 or more hours per day are susceptible to the development of PIU [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further research has suggested that IA is associated with relevant psychological impairment, such as psychopathology, serious mental illness including depression and anxiety [ 10 ], and suicidality [ 10 ]. Common significant predictors of IA include age (being < 35 years), being male, using the internet > 5 h daily, having no children, having secondary employment [ 11 ], taking illicit drugs, being diabetic [ 12 ], dysfunctional emotional regulation [ 13 ], loneliness [ 14 ], lower levels of self-control and higher levels of foreclosed and diffuse identity [ 15 ], low education among parents, lifetime tobacco use [ 16 ], social connectedness, social media addiction, digital game addiction and smartphone addiction [ 17 ], low self-esteem [ 18 ], and low emotional intelligence [ 19 ].…”
Section: Introductionmentioning
confidence: 99%